Aplikasi Canva Sebagai Media Pembelajaran yang Menarik di Era Digital - Dwi Nur Indah Sari; Wahyu Sugiarto; Rahma Sabilla; Alfi Zidanurrohim; Aswin Nurjanah; Muh. Alif Kurniawan (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
In the current digital era, all elements are required to adapt to technological developments, one of which is in the world of education. The success of education cannot be separated from interesting learning media. Especially in the current era, there are many applications that can support the learning process. One of them is the Canva application as explained in this article. The aim of writing this article is to make educators more aware of technological advances, especially the use of the Canva application in learning in the current digital era. In this article the author uses a library research method, namely by collecting data through various library sources such as journals, books and other scientific sources that are relevant to the topic discussed in this article. The results of this research are that the Canva application is an interesting application to use as a learning medium. Because in the Canva application there are various interesting features that support the learning process.